Analisis Kritis Terhadap Teknik-Teknik Penerjemahan dalam Alih Bahasa Arab–Indonesia - Yeniati Ulfah; Rizka Anugrah (Universitas KH. Mukhtar Syafaat, 2026)
This study aims to examine the translation techniques commonly employed in translating Arabic texts into Indonesian. Utilizing a qualitative methodology with a library research approach, this research draws data from various literature sources, including academic books and peer-reviewed journals that discuss Arabic–Indonesian translation practices. The data were analyzed using content analysis techniques to classify and interpret the types of translation methods identified. The findings reveal that M. Faisol Fatawi identifies seven translation techniques, Muhammad Apridho outlines eighteen, and Thalhah notes sixteen techniques. Among these, several techniques frequently appear across different works, particularly borrowing, calque, adaptation, and literal translation. These techniques are widely adopted by translators due to their applicability and consistency in preserving meaning and linguistic structure between source and target texts.